Unleashing Charisma: The Impact of Bing Dwen Dwen On National Identity and Tourism In China - Lenial, Lovjoyla Belinda; Willyam, Selena Cheryl; Wardaya, Marina (VCD: Journal of Visual Communication Design, 2025)
Bing Dwen Dwen is a panda mascot that became the official mascot for Beijing’s 2022 Winter Olympics in China. This research aims to identify and recognize the main factors that make Bing Dwen Dwen, popular and very eye-catching. Its charm attracts people from around the world and thus the second objective of this research is to analyze its impact on the tourism industry. Through qualitative and quantitative approaches, this research uses case studies, interviews with experts, and visitor surveys to reveal design elements and marketing strategies that contribute to the success of Bing Dwen Dwen. From all the approaches conducted, it is found that an attractive and relevant mascot design can effectively reflect cultural values, traditions, and unique characteristics of a country. Such mascots could also gain emotional attachment from the public, making the people have pride with their own country’s emblem or symbol representation. The mascot's popularity also plays a role in strengthening China's national image and increasing its tourism appeal at the global level. Further analysis revealed that visual elements, such as color and shape, have a significant influence on people's perceptions. The implications of this research emphasize the importance of strategic planning in mascot development, including public involvement and collaboration with experienced designers. The discovery provided insights for Indonesia in designing and creating tourism branding strategies, as well as strengthening national identity through mascots as a practical cultural promotional element.